Acoustic immittance measures basic and advanced practice - Hunter, Lisa L.; Shahnaz, Navid (Plural Publishing, Inc., 2014)
This book provides an accessible and easy to understand treatment of acoustic immittance, from basic to advanced measures. Laboratory exercises and clinical cases from actual practice are provided, with focused questions to elicit classroom discussion
Keywords: Audiometry, Impedance; Acoustic Impedance Tests / methods; Hearing Disorders / diagnosis